ANTIOXIDANTACTIVITY OF POLYPHENOLS FROM TOONA SINENSIS ROEM SEEDS AND THE INHIBITION OF ALDOSE REDUCTASE - Wang, Xiaohong; Li, Wanzhong (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: The seeds of Toona sinensis (Juss.) M. Roem (T. sinensis) have long been used in Traditional Chinese Medicine for the treatment of diabetes mellitus (DM) and its complications. The aim of this study was to investigate the antioxidant activity of different polyphenols fractions from Toona sinensis Roem (T. sinensis) seeds (PTSS) and the inhibition of aldose reductase (AR). Methods: Macroporous resin was used to purify PTSS, and the antioxidant activities were evaluated with total antioxidant capacity and free-radical scavenging. AR inhibitory activities were investigated by employing various established systems. Results: The polyphenol eluted by 60% alcohol (PTSS3) exhibit the highest antioxidant activity and AR inhibition, with an r value of 0.9924 ± 0.0066 in correlation analysis. The inhibition mechanism of PTSS3 on AR is uncompetitive inhibition. Conclusion: This research demonstrates that PTSS offers potential for intervening diabetes mellitus and its complications.